Evidence Based Nursing Self-Management untuk Mengurangi Konstipasi pada Pasien Kanker Payudara yang Menjalani Kemoterapi: A Literature Review - Annisa Nur laili; Rofianto Adi Prasetyo; Herna Slamet Nuryana; Uti Uswatun Nisa; Nur Istiqomah (Journal of Bionursing, 2021)
Introduction: Breast cancer is a protrusion or abnormal growth in the breast area, cancer patients are usually treated with chemotherapy. In the administration of chemotherapy, especially the frequency of administration can cause several effects such as nausea, vomiting, constipation, weight loss, loss, diarrhea, changes in taste, and changes in emotions. Method: Search journal articles electronically through several databases including Google Scholar, Science Direct, Proquest, and Pubmed. Search is done using English that is relevant to the topic. The keywords used are "constipation / self constipation, self management / chemotherapy / chemotherapy, breast cancer / breast cancer" and found 5 articles to be reviewed based on the PICO framework. Results: the application of self management has proven effective, easy to do, safe and technically practical to reduce constipation in breast cancer patients because it does not require special skills or training to do so. Self management can be used as a non-pharmacological therapy. Discussion: the use of self management methods which include abdominal massage, abdominal streching, and health promotion related to the position of the right defecation is believed to be effective for reducing constipation. The mechanism that is carried out is stimulating or giving a sensation in the abdominal area by massaging. The use of self management does not cause significant obstacles and adverse effects. Conclusion: self management can reduce constipation due to chemotherapy.